The Buddha of Suburbia - Kureishi, Hanif 1954- (Faber and Faber, 1990)
The Buddha of Suburbia, Hanif Kureishi's first novel, is a tour de force of comic invention, a bizarre, often hilarious, and totally original picture of the life of a young Pakistani growing up in 1970s Britain. Karim lives with his Mum and Dad in a suburb of south London and dreams of making his escape to the bright lights of the big city. But his father is no ordinary Dad, he is 'the buddha of suburbia', a strange and compelling figure whose powers of meditation hold a circle of would-be mystics spellbound with the fascinations of the East. Among his disciples is the glamorous and ambitious Eva, and when 'the buddha of suburbia' runs off with her to a crumbling flat in Barons Court, Karim's life becomes changed in ways that even he had never dreamed of...
Keywords: Fiction in English, 1945- - Texts; Romans (teksten); Boys -- Fiction; East Indians -- England -- Fiction; Fathers and sons -- Fiction; London (England) -- Fiction; Fiktionale Darstellung; Bildungsromans; Domestic fiction